Integrated photooxidative extractive deep desulfurization using metal doped TiO2 and eutectic based ionic liquid - Zaid, H.F.M. (American Institute of Physics Inc., 2016)
A series of metal doped TiO2 namely Fe/TiO2, Cu/TiO2 and Cu-Fe/TiO2 were synthesized and characterized, to be used as a photocatalyst in the integrated photooxidative extractive deep desulfurization for model oil (dodecane) and diesel fuel. The order of the photocatalytic activity was Cu-Fe/TiO2 followed by Cu/TiO2 and then Fe/TiO2. Cu-Fe/TiO2 was an effective photocatalyst for sulfur conversion at ambient atmospheric pressure. Hydrogen peroxide was used as the source of oxidant and eutectic-based ionic liquid as the extractant. Sulfur conversion in model oil reached 100. Removal of sulfur from model oil was done by two times extraction with a removal of 97.06 in the first run and 2.94 in the second run. Â© 2016 Author(s).